A Policy Output Model of Interorganizational Relations - Joseph A. Raelin (Organization Studies, 1982)
A model if proposed for studying the effect of interorganizational relations upon the quality of network performance under mandated legislation. The research applies the interorganizational constructs to a substantive public policy setting. In particular, it is concerned with the nature of interorganizational relations among actors who have been brought together on the basis of a legal-political mandate.
Keywords: D85; L14; M10; 330; Interorganizational relations; Mandated networks; Public sector networks